Production Track Balance Design To Minimize Bottleneck - Mustika Sari (Journal Basic Science and Technology, 2021)
PT. Socfin Indonesia Kebun Tanah Belih is a company engaged in rubber processing with crumb rubber products. In the production process there is a bottleneck problem. Aims to get an improvement in the balance of the production line so as to increase production output. The right problem solving method is the Ranked Position Weight method, Theory of Constraints, and the Simulated Annealing Algorithm. RPW is used to calculate the actual production line performance. The results obtained indicate that there is an imbalance in the path, then an analysis of the causes of the problem is carried out using the TOC method. The results of the cause of problems at the work station and the reduction of the time of the work elements are obtained, so that the smoothing index value is obtained as a path balance parameter. The smoothing index value is then used as the initial solution in the Simulated Annealing Algorithm. The parameters of the Simulated Annealing Algorithm include cycle time, initial temperature of 1000C, 17 iterations, and steady state termination at N value of 3. The search for new solutions is carried out by iterating by combining work elements based on precedence diagrams and zoning constraints. The iteration stops when N is 3, meaning that the iteration has been rejected three times in a row. The best solution is obtained in iteration 10 with a value of 110.39. By using the Simulated Annealing Algorithm method, the efficiency value is increased by 9.36%, the balance delay value decreases by 9.36% and the smoothing index decreases by 94.18.